2023
DOI: 10.1371/journal.pntd.0011447
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles produced by Zingiber officinale ameliorates acute toxoplasmosis-induced pathological and biochemical alterations and reduced parasite burden in mice model

Abstract: Background Although, approximately 30% of the world’s population is estimated to be infected with Toxoplasma gondii (T. gondii) with serious manifestations in immunocompromised patients and pregnant females, the available treatment options for toxoplasmosis are limited with serious side effects. Therefore, it is of great importance to identify novel potent, well tolerated candidates for treatment of toxoplasmosis. The present study aimed to evaluate the effect of Zinc oxide nanoparticles (ZnO NPs) synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…These results align with the findings of Akbar et al, 55 who reported robust antibacterial effects of ZnO-NPs against Salmonella typhimurium and S. aureus . 58 60 Moreover, other studies have demonstrated the potent bactericidal and antifungal activities of ZnO-NPs against a spectrum of pathogens. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…These results align with the findings of Akbar et al, 55 who reported robust antibacterial effects of ZnO-NPs against Salmonella typhimurium and S. aureus . 58 60 Moreover, other studies have demonstrated the potent bactericidal and antifungal activities of ZnO-NPs against a spectrum of pathogens. 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…To date, only one study, recently published in 2023, has addressed this topic ( 23 ). In this study, researchers used the ginger ethanolic extract to produce ZnO-NPs by combining it with sodium hydroxide and zinc acetate.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, researchers used the ginger ethanolic extract to produce ZnO-NPs by combining it with sodium hydroxide and zinc acetate. These ZnO-NPs were then assessed for their effectiveness against T. gondii RH strain in infected mice ( 23 ). In alignment with our findings, their study similarly discovered that mice treated with ZnO-NPs exhibited a notably extended survival rate and decreased parasite burden in comparison to untreated mice or those treated with spiramycin ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations